U.S. Census Bureau‐assessed prevalence of anxiety and depressive symptoms in 2019 and during the 2020 COVID‐19 pandemic - Twenge, Jean M.; Joiner, Thomas E. (Depression and anxiety, 2020)
Background The disruptions to daily life caused by the coronavirus disease 2019 (COVID‐19) pandemic may have impacted mental health, particularly mood disorders. This study aimed to compare prevalence rates of anxiety disorder and depressive disorder in national samples in the U.S. before and during the pandemic. Methods Participants (n = 336,525) were from U.S. Census Bureau‐administered nationally representative probability samples, one from the first half of 2019 and four during the pandemic in April and May 2020. All participants completed the Patient Health Questionnaire‐2 screening for depressive disorder and the Generalized Anxiety Disorder‐2 screening for anxiety disorders. Results Compared to U.S. adults in 2019, U.S. adults in April and May 2020 were more than three times as likely to screen positive for depressive disorders, anxiety disorders, or one or both, with more than one out of three screening positive for one or both. The prevalence of anxiety decreased slightly between the April 23–May 4, 2020 and the May 21–26, 2020 administrations, while the prevalence of depression increased slightly. Conclusions U.S. adults in 2020 are considerably more likely to screen positive for mood disorders than in 2019, with anxiety declining and depression increasing from April to May.